Bank Cost Efficiency in Hong Kong and China - Lei, Juan (2013)
Applying stochastic frontier cost function, this paper examines banks cost efficiency in Hong Kong and China from the period of 1993 to 2012. One main purpose of this paper is to investigate how banks perform differently between Hong Kong and China. A second step regression analysis is also conducted in the frontier to check deterministic factors of cost efficiency. Overall, the yearly mean efficiency ranges from 0.57 to 0.83. Compared with Hong Kong, Chinese banks seem to be holistic more efficient but the top ten efficient banks all come from Hong Kong. In the regression results, unconsolidated banks exhibit more cost efficiency than consolidated banks. And the variables INFL (inflation rate), NIM (net interest margin), ROAE (return on average equity) and CTIR (cost to income) indicate positive relationship with inefficiency while LNTA (logarithm of total assets) ETA (equity to total assets) demonstrate negative relationship with the inefficiency term.